2018
DOI: 10.3390/ma11081318
|View full text |Cite
|
Sign up to set email alerts
|

The Heat Treatment Influence on the Microstructure and Hardness of TC4 Titanium Alloy Manufactured via Selective Laser Melting

Abstract: In this research, the effect of several heat treatments on the microstructure and microhardness of TC4 (Ti6Al4V) titanium alloy processed by selective laser melting (SLM) is studied. The results showed that the original acicular martensite α′-phase in the TC4 alloy formed by SLM is converted into a lamellar mixture of α + β for heat treatment temperatures below the critical temperature (T0 at approximately 893 °C). With the increase of heat treatment temperature, the size of the lamellar mixture structure insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 36 publications
2
39
0
Order By: Relevance
“…Although the increase in joining temperature could give rise to the grain growth of TC4, resulting in hardness decrease, it was clarified that the microhardness of TC4 gradually decreased with temperature only when it was lower than the phase transformation temperature of 882 °C . Instead, microhardness increased with annealing temperature when it was higher than 882 °C due to the martensite transformation of β ‐Ti . Thus, the brazing temperature of 980 °C with Cu‐50TiH 2 filler may lead to a slight increase in the microhardness of the TC4 alloy.…”
Section: Resultsmentioning
confidence: 99%
“…Although the increase in joining temperature could give rise to the grain growth of TC4, resulting in hardness decrease, it was clarified that the microhardness of TC4 gradually decreased with temperature only when it was lower than the phase transformation temperature of 882 °C . Instead, microhardness increased with annealing temperature when it was higher than 882 °C due to the martensite transformation of β ‐Ti . Thus, the brazing temperature of 980 °C with Cu‐50TiH 2 filler may lead to a slight increase in the microhardness of the TC4 alloy.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the extension of the deposition plane and to the heating caused by the layers overlapping, cooling condition are not so severe to led to a martensitic microstructure. Unlike EB-PBF, L-PBF gives rise to more severe cooling and consequently to the formation of the α martensite [53]. hardening of titanium by quenching is only moderate.…”
Section: Metallographic Investigationmentioning
confidence: 99%
“…The demand for Titanium alloy (Ti6Al4V) dominates in various fields including aerospace, marine, automobile, chemical, and biomedical industries [1][2][3][4][5][6]. This widespread use of Grade 5 Ti6Al4V is as it possesses high specific strength, high fracture toughness, ductility, excellent corrosion, and fatigue resistance, high-level biocompatibility, good damage tolerance, workability, etc.…”
Section: Introductionmentioning
confidence: 99%
“…After heat treatment, the alloy achieve superior tensile thermo-mechanical behavior. Several authors [6,[20][21][22][23][24] discussed the effect of various heat-treatment procedures on the microstructure, hardness and tensile properties of Ti6Al4V. Gao et al [25] concluded that the annealing treatment decreases the fatigue life of Ti6Al4V.…”
Section: Introductionmentioning
confidence: 99%